in the equation: y=mx+b , the y-intercept is represented by "b".
same thing. but its easy to change y=b+mx to y=mx+b
Symmetry, which states that if A = B then B = A Put A = 4 and B = x + y
b is the intercept through the y axis
b stands for the y-intercept
If: A = Y+B Then: -Y = -A+B or Y = A-B
y = (3 X 8) - 5 = 21.
in the equation: y=mx+b , the y-intercept is represented by "b".
the y-1 is a minus .
y = mx + b y - mx = b
same thing. but its easy to change y=b+mx to y=mx+b
y = mx + b
Symmetry, which states that if A = B then B = A Put A = 4 and B = x + y
b = y - mx.
b is the intercept through the y axis
b stands for the y-intercept
x + y + z = 0 x = a - b, y = b - c, z = c - a, therefore a - b + b - c + c - a = ? a - a + b - b + c - c = 0